Right place. Right time. Right tool: guidance for using target analysis to increase the likelihood of invasive species detection - Jeffrey T. Morisette; Jamie K. Reaser; Gericke L. Cook; Kathryn M. Irvine; Helen E. Roy (Biological Invasions, 2020)
In response to the National Invasive Species Council’s 2016–2018 Management Plan , this paper provides guidance on applying target analysis as part of a comprehensive framework for the early detection of and rapid response to invasive species (EDRR). Target analysis is a strategic approach for detecting one or more invasive species at a specific locality and time, using a particular method and/or technology(ies). Target analyses, which are employed across a wide range of disciplines, are intended to increase the likelihood of detection of a known target in order to maximize survey effectiveness and cost-efficiency. Although target analyses are not yet a standard approach to invasive species management, some federal agencies are employing target analyses in principle and/or in part to improve EDRR capacities. These initiatives can provide a foundation for a more standardized and comprehensive approach to target analyses. Guidance is provided for improving computational information. Federal agencies and their partners would benefit from a concerted effort to collect the information necessary to perform rigorous target analyses and make it available through open access platforms.

Comparison of four modeling tools for the prediction of potential distribution for non-indigenous weeds in the United States - Roger Magarey; Leslie Newton; Seung Cheon Hong; Yu Takeuchi; David Christie; Catherine S. Jarnevich; Lisa Kohl; Martin Damus; Steven I. Higgins; Leah Millar; Karen Castro; Amanda West; et al. (Biological Invasions, 2018)